Catalytic activity of catalase–silica nanoparticle hybrids: from ensemble to individual entity activity. Issue 3 (20th December 2016) - Chan, Crystal; Sepunaru, Lior; Sokolov, Stanislav V.; Kätelhön, Enno; Young, Neil P.; Compton, Richard G.
Abstract : We demonstrate the electrochemical detection and characterization of individual nanoparticle–enzyme hybrids. Abstract : We demonstrate the electrochemical detection and characterization of individual nanoparticle–enzyme hybrids. Silica nanoparticles were functionalized with catalase enzyme and investigated spectroscopically and electrochemically. The catalytic activity of the hybrids towards hydrogen peroxide decomposition was comparable to the activity of a freely diffusing enzyme in solution, exhibiting a Michaelis–Menten constant of K M = 74 mM and a turnover number of k cat = 8 × 10 7 s −1 per NP. The fast turnover number of the hybrid further enabled the electrochemical detection of individual nanoparticle–enzyme hybrid via a novel method: the hydrogen peroxide substrate was generated at a microelectrode which enabled enzymatic activity exclusively within the diffusion layer of the electrode. The method is the first electrochemical approach for measuring hybrid nanoparticles, at the single entity level.